Synthesis and characterization of silicon nanowires - Long, Shihong. (2009)
Silicon nanowires have been proven to exhibit interesting properties different from their bulk counterparts. Due to the decrease in size, many applications can utilize silicon nanowires’ unique properties in the ever-shrinking electrical components today.